(untitled) (Brazilian Journal of Health Research, 2023)
Introduction: Osteomyelitis has become an increasingly common pathology in Brazil due to the progressive increase in high-impact traumas with consequent severe fractures, and its management is a major challenge for health professionals. Objective: to characterize the etiology and microbiological profile of osteoarticular infections in a public hospital in the state of Espírito Santo - Brazil. Methods: 180 patients were included in the study, with 231 bacterial strains isolated. Results: Of the 231 strains, 57.1% were Gram positive bacteria, with methicillin-resistant Staphylococcus aureus (S. aureus) being the most prevalent agent. Of the gram negative strains, Pseudomonas aeruginosa (P. aeruginosa) and Acinetoabcter baumannii (A. baumannii) were the most prevalent. Conclusion: gram positive cocci such as S. aureus and Coagulase negative staphylococcus predominate as etiologic agents of chronic osteomyelitis with a high prevalence of MRSA among the Staphylococcus strains in the study population. Among the strains of gram negative bacteria, P. aeruginosa and A. baumannii predominate, with high resistance to cefepime and good sensitivity to amikacin.